Interactive visualisation of algebraic surfaces as a tool for shape creation. (25th April 2011) - Stussak, Christian; Schenzel, Peter
Mathematical models gain an increasing interest as a source of inspiration for applications in fine art, design and architecture. Here, we investigate implicitly defined algebraic surfaces to create interesting looking and often very beautiful objects. Interactive and real time visualisation can help to explore the full potential of such surfaces. For this purpose we provide our tool REALSURF, which uses modern graphics processor programming techniques to achieve real time visualisation performance. We give a brief introduction to the underlying algorithms and we will show several approaches, that aid the process of designing interesting algebraic surfaces.